Long-Term Effect of Adverse Childhood Experiences, School Disengagement, and Reasons for Leaving School on Delinquency in Adolescents Who Dropout - Bae, Sung Man (Frontiers in Psychology, 2020)
Purpose: The purpose of this study was to verify the long-term effect of adverse childhood experiences, school disengagement, and the reasons for leaving school on adolescent delinquency while adjusting for sex. Methods: Data were collected from 663 teenagers (male 368, female 295; mean age = 16.81 [SD=1.10]; age range=13-19 years) through a Longitudinal Survey and Support Plan for Dropouts. Results: Multivariate latent growth modeling demonstrated that adverse childhood experiences and school disengagement are positively associated with delinquency and the mediating effect of school disengagement on association between adverse childhood experiences and delinquency was verified. Teenagers who quit school for personal reasons reported fewer instances of delinquent behavior than adolescents who left because of school reasons. Conclusions: This study suggests that researchers and teachers need to consider adverse childhood experiences and school disengagement as a warning index for delinquency with school dropout. In addition, the reason for leaving school should be considered to clarify the effect of school dropout on delinquency in adolescents who drop out.